PROFIL BIOMOTOR ATLET PORPROV WUSHU TAOLU DI SASANA GENTA SUCI AMBARAWA, KABUPATEN SEMARANG - Arif Wicaksono; Amin, Nur (Plyometric: Jurnal Sains dan Pendidikan Keolahragaan, 2023)
Good physical condition supports achievements, especially in the sport of wushu. Biomotor components are strength, speed, explosive power, flexibility, agility, endurance and balance. According to the interview, the trainer only studied the endurance component. The researcher's aim is to examine all bimotor components. This research uses quantitative descriptives with a cross sectional design, to collect data using tests and measurements. There were 9 sample athletes with the criteria of wushu athletes taking part in Porprov 2023 who were aged 16-18 years, using purposive sampling. The instruments used are strength: push ups and sit ups, speed: 30 meter run, flexibility: sit and reach, endurance: 2.4 km run, explosive power: vertical jump, agility: 10 meter back and forth run and balance: stand one legs as long as possible.. The research results showed that the bimotor profile of Porprov wushu taolu athletes was that male arm muscle strength was in the moderate category at 33.3% and abdominal muscle strength was in the poor category at 66.7%. Women's arm muscle strength is in the moderate category at 100% and abdominal muscle strength is in the moderate category at 66.7%. Men's explosive power is in the moderate category at 50.0%, women's explosive power is in the very good category at 66.7%. Men's flexibility is in the very good category at 66.7%, women's flexibility is in the moderate category at 66.7%. Men's speed was in the good category at 83.3%, women's speed was in the good category at 100%. The balance of men is in the good category at 83.3%, the balance for women is in the very good category at 66.7%. Male agility is in the good category at 83.3%, female agility is in the moderate category at 100%. Men's endurance is in the moderate category at 66.7%, women's endurance is in the medium category at 100%. From the data above, it can be concluded that from the results of the overall average profile of Proprov wushu taolu athletes at Sasana Genta Suci Ambarawa, Semarang Regency, they are in the good category.